The neotropical genera Microthereva Malloch and Peralia Malloch (Diptera: Therevidae: Therevinae) - Webb, Donald W. (Zootaxa, 2006)
The Neotropical stiletto fly genera Microthereva Malloch and Peralia Malloch are revised. These two genera from Argentina and Chile belong to the Anabarhynchus genus group of lower Therevinae. Dialineura costalis Bigot, Anabarhynchus grisea Kröber, Anabarhynchus maculifrons Kröber, Anabarhynchus niger Bigot, and Thereva schineri Jaennicke are synonomized under Peralia vittata Philippi. Each species is redescribed with illustrations of their genitalia, a key to their identification, and a map of their distribution.